2005
DOI: 10.1002/andp.200510145
|View full text |Cite
|
Sign up to set email alerts
|

Proof of perturbative gauge invariance for tree diagrams to all orders

Abstract: It is proved that classical BRS-invariance of the Lagrangian implies perturbative gauge invariance for tree diagrams to all orders. The proof applies in particular to the Einstein Hilbert Largrangian of gravity.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 34 publications
4
23
0
Order By: Relevance
“…The theorem in [45] of course fits with our construction. The previous analysis allows one next 2 Some of the authors of that reality check openly suspected SSB as a formal recipe without physical meaning; others were swayed by the remarkable "success rate" of the Higgs mechanism; some apparently remained agnostic.…”
Section: Outline Of the Sequelsupporting
confidence: 61%
See 2 more Smart Citations
“…The theorem in [45] of course fits with our construction. The previous analysis allows one next 2 Some of the authors of that reality check openly suspected SSB as a formal recipe without physical meaning; others were swayed by the remarkable "success rate" of the Higgs mechanism; some apparently remained agnostic.…”
Section: Outline Of the Sequelsupporting
confidence: 61%
“…The first method is constructive. The second, stemming from a theorem by one of us in [45], is useful rather to verify CGI. Section 3 summarizes the first results of the theory.…”
Section: Outline Of the Sequelmentioning
confidence: 99%
See 1 more Smart Citation
“…(The corresponding renormalization map D (3.22) is given in [27].) Our definitions of T c tree (4.8) and Ttree (4.10) do not contain this 1/2 g µν δ-term, in agreement with the definition of R cl (2.17).…”
Section: Diagrammatics and Definition Of The 1-particle-irreducible Psupporting
confidence: 58%
“…The violation of the conservation of j(g) is expressed in terms of the Q-vertex [13,2,1]: in Sects. 3 and 4 of [27] it is shown that for the considered models there exists a Q-vertex L (1) (g) such that…”
Section: Assumption: Localized Off-shell Version Of Noether's Theoremmentioning
confidence: 99%